2014
DOI: 10.1007/s40195-014-0173-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologically Induced Corrosion of X80 Pipeline Steel in a Near-Neutral pH Soil Solution

Abstract: MIC of X80 pipeline steel in a near-neutral pH soil solution in the presence and absence of sulfate-reducing bacteria (SRB) was monitored by electrochemical techniques and microbiological tests. The results show that soil solution is more close to the complex soil environment around pipeline. The activity of SRB leads to the shift of the phase response to low frequency, the decrease of electrolyte resistance and the alteration of dielectric constant of the film. Both the activity and metabolite of SRB influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 33 publications
(60 reference statements)
2
10
0
Order By: Relevance
“…4). These lower measured potentials of A. fulgidus-inoculated media correspond to an accelerated corrosion process (Venzlaff et al, 2013;Wu et al, 2015;Raman et al, 2008;Cheng et al, 2009;Alfaro-Cuevas-Villanueva et al, 2006), confirmed by our measured current densities. It could be related to intense microbial activity (Cheng et al, 2009) and correlated to the SEM and AFM observations (Figs.…”
Section: Discussionsupporting
confidence: 84%
“…4). These lower measured potentials of A. fulgidus-inoculated media correspond to an accelerated corrosion process (Venzlaff et al, 2013;Wu et al, 2015;Raman et al, 2008;Cheng et al, 2009;Alfaro-Cuevas-Villanueva et al, 2006), confirmed by our measured current densities. It could be related to intense microbial activity (Cheng et al, 2009) and correlated to the SEM and AFM observations (Figs.…”
Section: Discussionsupporting
confidence: 84%
“…As a result, during the fretting wear process, abrasion is not the only damage, microstructure changes, including nano-grain layer, deformation slips with high residual strain concentration and even micro-cracks will also have a detrimental effect to the service performance of the heat exchanger tubes in NPPs. For instance, high residual strain concentration and deformation slips will promote the SCC or fatigue initiation and propagation in nickel-based alloys and stainless steels in HTHP water [36,37].…”
Section: Potential Effects Of Wear Damage On Further Performance Of Tmentioning
confidence: 99%
“…Sulfate-reducing bacteria (SRB) are anaerobic bacteria, which can be found in 1 3 oxygen-deficient soils. SRB can increase the corrosion process by producing hydrogen sulfide and transform non-corrosive soil into highly corrosive soil [8]. Li et al [9] found that Brevibacterium halotolerans promote the corrosion of X80 steel.…”
Section: Introductionmentioning
confidence: 99%